2021
DOI: 10.1111/acel.13413
|View full text |Cite
|
Sign up to set email alerts
|

Cell nonautonomous roles of NHR‐49 in promoting longevity and innate immunity

Abstract: Recent advances in aging research have led to a shift in focus from increasing life span to improving health span, a concept that encompasses measures of physiological health, including stress resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 92 publications
(184 reference statements)
4
41
0
Order By: Relevance
“…As described above, NHR-49::GFP imaging indicated that NHR-49 protein levels are induced in the intestine, neurons, and hypodermis during hypoxia ( Figure 2D , Figure 2—figure supplement 1E and F ). Hence, we asked if the expression of NHR-49 in any one of these tissues could rescue the hypoxia survival defects of the nhr-49 mutant ( Naim et al, 2021 ). Comparing the survival of each tissue-specific NHR-49::GFP rescue strain to their respective non-GFP siblings, we found that expressing nhr-49 in the intestine, neurons, hypodermis, body wall muscle, or from its endogenous promoter was sufficient to restore population survival to wild-type levels ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As described above, NHR-49::GFP imaging indicated that NHR-49 protein levels are induced in the intestine, neurons, and hypodermis during hypoxia ( Figure 2D , Figure 2—figure supplement 1E and F ). Hence, we asked if the expression of NHR-49 in any one of these tissues could rescue the hypoxia survival defects of the nhr-49 mutant ( Naim et al, 2021 ). Comparing the survival of each tissue-specific NHR-49::GFP rescue strain to their respective non-GFP siblings, we found that expressing nhr-49 in the intestine, neurons, hypodermis, body wall muscle, or from its endogenous promoter was sufficient to restore population survival to wild-type levels ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies indicate that stress response regulation requires the intricate interactions of multiple factors as part of networks that provide regulatory redundancy and flexibility. NHR-49 is a transcription factor that promotes longevity and development by regulating lipid metabolism and various stress responses ( Chamoli et al, 2014 ; Dasgupta et al, 2020 ; Goh et al, 2018 ; Naim et al, 2021 ; Wani et al, 2021 ). Our data show that NHR-49 coordinates a part of the transcriptional response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations